Harnessing agri-food system microbiomes for sustainability and human health - Fernández-Gómez, Paula; Leong, Dara; Berg, Gabriele; Brennan, Fiona; Caruso, Tancredi; Charles, Trevor C.; Cocolin, Luca S.; Lange, Lene; McAuliffe, Olivia; Maguin, Emmanuelle; O’Sullivan, Orla; Sanz, Yolanda; et al. (Frontiers in Science, 2025)
Food system microbiomes include complex microbial networks that range from soil and marine environments to primary agriculture, farming, food processing, and distribution, and which influence human and environmental health. Advances in “omics” technologies, such as metagenomics, metatranscriptomics, metaproteomics, metabolomics, and culturomics, and their integration have deepened our understanding of microbiome dynamics and interactions. This growing knowledge is being leveraged to develop microbiome-based solutions enabling more sustainable food systems. This review explores microbiome interconnections along the food system and how this and other knowledge relating to microbiomes can be harnessed to, among other things, enhance crop resilience and productivity, improve animal health and performance, refine management practices in fishing and aquaculture, or prolong shelf life and reduce food spoilage during distribution. The often-overlooked role of bacteriophages on shaping microbiomes is discussed, as is the impact of diet on the human gut microbiota and, in turn, health. Despite advances, knowledge remains incomplete in particular areas and targeted experimental approaches are necessary to fill these gaps—going beyond merely predicting microbiome functionality. Ultimately, the ideal development of microbiome-based innovations in food systems will require collaboration between stakeholders and regulators to ensure safety, efficacy, and widespread adoption, unlocking its full potential to improve the health of animals, humans and the environment globally.